Law No.176 of the year 2018 Promulgating the Law Regulating Financial Lease and Factoring Activities = قانون تنظيم نشاطي التأجير التمويلي والتخصيم. (2025)
1. General Provisions -- 2. Financial lease activity -- 3. Factoring activity -- 4. Federations -- 6. Supervision and Protection of Dealers -- 7. Penalties -- 8.